A review of the subfamily Rogadinae (Hymenoptera: Braconidae) from Iran - Farahani, Samira; Talebi, Ali Asghar; Achterberg, Cornelis Van; Rakhshani, Ehsan (Zootaxa, 2015)
Specimens of the subfamily Rogadinae (Hymenoptera: Braconidae) were collected in northern Iran during 2010–2011 with a series of Malaise traps. Twelve species belonging to three genera (Aleiodes Wesmael, 1838, Heterogamus Wesmael, 1838 and Clinocentrus Haliday, 1833) were identified, with one genus (Heterogamus) and seven species new for the fauna of Iran. An updated checklist of the genera and species of the subfamily Rogadinae is included. A total of 26 species belonging to four genera are listed for Iran after correction for misidentifications. A key to the genera and the species of Rogadinae known from Iran is provided.